Cumulative risk, the cognitive home environment and vocabulary in early childhood. (9th January 2020) - Shriver, Amy E.; Bonnell, Levi N.; Berman, Stephen; Camp, Bonnie W.
Abstract: Introduction: Early home support for language development is critical for later developmental progress. Paediatricians have the opportunity to identify families at risk of failing to provide this support in infancy but often lack simple tools to do so. This study explores the potential of a simple count of sociodemographic risk factors, a cumulative risk (CR) index, to identify families likely to need help in providing literacy support from an early age. Methods: CR scores were calculated for 308 families who completed the STIMQ and MacArthur Communicative Development Inventory (MCDI) at 11–15 months) and 197 (64%) again at 23–37 months. Analysis of variance with linear contrasts examined the effect of CR on the STIMQ and the MCDI at baseline and follow‐up. Correlation analysis explored the relationship between STIMQ and MCDI. Results: At both baseline and follow‐up, CR index showed a significant effect ( p <0.006) on the STIMQ along with a significant linear trend for STIMQ scores to decrease as CR increased ( p <0.05–0.005). No significant effects of CR effects on MCDI were observed at baseline or follow‐up, whereas MCDI percentiles correlated significantly ( p <0.03–0.001) with STIMQ scores ( r =0.18–0.26.) at both times. Conclusions: The CR index is a simple tool that can help identify families needing support for providing a language stimulating home environment in the first 2 years before long‐term ill effects of sociodemographic barriers are established.